Identification of XPA and XPC gene mutations in patients with xeroderma pigmentosum - Rabie, Eman AbdelAlim Sidky (AUC Knowledge Fountain, 2016)
The human body employs different DNA repair pathways to protect itself against cancers induced by DNA damage. The nucleotide excision repair (NER) pathway comprises different synchronously working DNA repair proteins; two of which are XPA and XPC. Mutations of any of the genes encoding the NER proteins cause an autosomal recessive genetic disorder called Xeroderma Pigmentosum (XP). XP patients present with characteristic dry atrophic freckle-like pigmentation of the skin, photosensitivity and photophobia. Some patients develop neurodegenerative symptoms early in life, including mental retardation. Patients have a 10,000-fold increased risk for UV-induced skin cancers, moreover, a higher risk for ocular, oral and internal cancers. Death usually results from skin cancers, neurological deterioration, and internal cancers. XP is a rare disorder; it affects one per million individuals, however, higher incidences were observed in some geographical areas such as Mayotte islands (1:5000), Japan (1:22,000) and North Africa (1:10,000 in Tunisia and 1:80,504 in Morocco) due to geographical isolation, and high rate of intra-familial marriage. In North Africa, and in Egypt, XPC followed by XPA gene mutations are the most common. In Egypt, XP accounts for 15.9% of genetic skin disorders. Recently, XPA gene mutations were detected in four Egyptian XP patients only. In the current study, fourteen unrelated families having seventeen XP Egyptian patients were studied via direct sequencing for detection of both XPA and XPC gene mutations. This is the first study to identify mutations in both XPA and XPC genes in Egyptian XP patients with variable clinical features. Ten mutations were identified; four of which were recurrent mutations, three were novel mutations, and three mutations were reported previously in non-Egyptian XP patients. Carrier and prenatal screening were provided for the studied families. Spectra of XPA and XPC mutations in the Egyptian population were outlined with emphasis on clinical phenotypes. In conclusion, identification of pathogenic mutations provided a valuable tool for detection of recurring and private XP mutations in the Egyptian population. Mutation detection augments genetic counseling via carrier, prenatal and premarital screening, and provides a cornerstone for development of diagnostic strategies and future gene therapies.